On the struggle of the Roma for equal rights and the various forms this struggle has taken - Sadílková, Helena; Viková, Lada (Romano džaniben, 2024)
The introductory text to the monothematic issue focusing on the struggle of Romani people for equality, recognition and improved status within the societies in which they live highlights the various forms of this struggle. It recalls academic studies published on the topic of Romani emaciation in the Czech or Czechoslovak context, or texts in which the Romani actors themselves reflected on these topics. It covers a wide range of collective and individual activism, from the struggle for social recognition, efforts to join existing political structures, building Romani political movement, to initiatives aimed at improving the public perception of Roma, including the recognition of the Holocaust of Roma and Sinti and its inclusion in the collective historical consciousness. This issue of the journal presents the initiatives of specific Romani men and women from the Czech lands and Slovakia across the twentieth and twenty-first centuries who, through their involvement in social events, have become significant actors in variously directed initiatives and fellow combatants in this struggle for recognition, self-organisation and equality.
Keywords: Roma; Roma ethnoemancipation; Roma equality; Czech Republic; Slovak Republic